Structure Characterization and Antioxidant Activity of a Novel Polysaccharide from Bacillus natto Fermented Millet Bran - Hanzhuo Zhang; Xia Fan; Wenjie Zhao; Fanqiang Meng; Fengxia Lu; Zhaoxin Lu; Haizhen Zhao (Foods)
To improve the high-value application of millet bran, a water-soluble polysaccharide was extracted from fermented millet bran (FMBP) by using Bacillus natto fermentation. A neutral polysaccharide, FMBP-1, was separated and purified from FMBP using an anion exchange column. Its structure and antioxidant activity in vitro were characterized and determined. The molecular weight of FMBP-1 was 1.154 × 104 Da, and its molecular weight distribution was relatively uniform. The monosaccharide composition, FT-IR, methylation, and NMR results indicated that FMBP-1 was only composed of glucose and was an α-(1→4)-D-glucan that branched at O-6 with a terminal 1-linked α-D-Glcp as a side chain. In addition, the antioxidant assays indicated that FMBP-1 possessed certain capacities for scavenging free radicals and reducing power, and this was in a concentration-dependent manner. This research will provide fundamental data regarding the structure–activity relationship of millet bran polysaccharides and provide a theoretical foundation for the high-value utilization of millet bran within the food and pharmaceutical industries.